The Development and Characterization of a Cell Culture System from Indian Mud Crabs Scylla serrata. Issue 3 (22nd August 2019) - Sivakumar, Selvaraj; Raja Swaminathan, T.; Kumar, Raj; Kalaimani, Natarajan
Abstract: Commercially available culture media and supplements were tested for their potential to produce primary cell cultures from tissues of Indian mud crabs Scylla serrata . Eight commercially available culture media from Sigma‐Aldrich (Leibovitz's L‐15, Medium 199, Grace's Insect Medium, Minimal Essential Medium, Dulbecco's Modified Eagle Medium, TC‐100 Insect Medium, IPL‐41 Insect Medium, and Roswell Park Memorial Institute) were examined. Three different supplements (amino acid and sugar [AS], crab muscle extract [CME], and natural seawater [NSW]) were also examined. The hemocyte culture appeared to grow well for a maximum period of 21 d in 2 × L‐15 medium supplemented with AS and 15% fetal bovine serum (FBS). Partial amplification and sequencing of the cytochrome oxidase subunit I (COI) gene confirmed that the primary hemocytes originated from Indian mud crabs. The effects of four metals on hemocyte viability were evaluated using the MTT assay. Of the four metals examined (arsenic, lead, cobalt, and nickel), cobalt and nickel were more toxic to the crab cells than the other metals. Both acridine orange/ethidium bromide and Hoechst staining showed the presence of apoptosis and necrosis in metal‐treated groups, which suggests that metals in an aquatic environment induce death of the Indian mud crab's hemocytes. The hemocyte primary cell culture was also used to study the cytotoxicity effect of bacterial extracellular products from Vibrio harveyi and white spot syndrome virus. This study demonstrates that hemocyte primary cell culture can be used as a tool to study viral and bacterial pathogenesis and to assess the cytotoxicity of pollutants present in aquatic environments.